1984
DOI: 10.1021/j150665a028
|View full text |Cite
|
Sign up to set email alerts
|

The photochemistry of 9,10-anthraquinone-2-sulfonate in solution. 2. Effects of inorganic anions: quenching vs. radical formation at moderate and high anion concentrations

Abstract: The chemical aspects of the interactions between excited 9,lO-anthraquinone-2-sulfonate (AQS) and various inorganic anions are examined. The anions which quench triplet AQS can be divided into two groups: Cl-, Br-, I-and NCS-(group I) photoreduce AQS to AQS-radical anion only at concentrations higher than that required for complete triplet quenching. The effect increases with concentration and passes through a maximum, with highest quantum yields of radical formation reaching N 1 for C1-and NCS-; on the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

1985
1985
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 0 publications
0
42
0
Order By: Relevance
“…Both the spectra of AQ in presence of DMA and DMDPM also exhibit peaks around 390 nm and 540 nm. It has been reported that 9,10-anthraquinone-2-sulfonate radical anion has l max at 385 nm and 510 nm [20,21]. So probably the peaks at 390 nm and 540 nm are due to the formation of AQ dÀ .…”
Section: Laser Flash Photolysis: Acetonitrile Mediummentioning
confidence: 97%
“…Both the spectra of AQ in presence of DMA and DMDPM also exhibit peaks around 390 nm and 540 nm. It has been reported that 9,10-anthraquinone-2-sulfonate radical anion has l max at 385 nm and 510 nm [20,21]. So probably the peaks at 390 nm and 540 nm are due to the formation of AQ dÀ .…”
Section: Laser Flash Photolysis: Acetonitrile Mediummentioning
confidence: 97%
“…[19] It is therefore most likely that the triplet excited-state chromophore 3 (Figure 2 b). By reference to the previous study, [21] this transient species is assigned to an AQS radical anion (AQSC À ). The AQSC À species formation gave a pseudo-first-order rate constant of 1.…”
Section: Resultsmentioning
confidence: 86%
“…Light-induced DNA cleavage or DNA adduct formation is greatly affected by co-existing chemicals [18,20,38,39]. Likewise, the photodegradation rate and the percent of each photoproduct are greatly affected by various factors [40][41][42][43]. Therefore, detailed mechanistic understanding on the photochemistry of PAHs is needed in order to determine the relationship between photomutagenicity and structure of the PAHs.…”
Section: Discussionmentioning
confidence: 99%